Anthropocenic After-life: Living Machines, Synthetic Biology and the End of Nature - Witek, Michał (Porównania, 2021)
The postulated arrival of the “Anthropocene era” and the “end of nature” widely discussed in humanities, as well as theoretical approaches such as nature-culture and techno-nature associated with this concept, open the door to redefining concepts such as “life”, “machine” or “biology”. This is visible both in the field of natural sciences, and transdisciplinary approaches such as synthetic biology as well as in experimental art. The purpose of this text is to look at the complex problem of “living machines” and “synthetic life” in the context of the speculative and critical potential of art and the postulated Anthropocene era in the works of Alexandra D. Ginsberg. The main problem is reflection on the vision of the role of “live machines” and “synthetic life” in the era of uncertainty and uncontrolled changes in the environment.